Laboratory diagnoses of the isolates of chestnut blight disease fungus Cryphonectria parasitica (MURR. BARR) - Radócz, László; Irinyi, László; Egyed, Károly (Acta Agraria Debreceniensis, 2010)
Chryphonectria parasitica, the casual agent of chestnut blight, is one of the most important fungal pathogens of chestnut (Castanea spp.) in Europe and Hungary. In this study, we analyzed the ITS region of five Cryphonectria parasitica strains isolated from different location of Hungary. The differences among the Cryphonectria parasitica isolates were not insignificant because only two sites were considered as informative for the parsimony analysis. As the differences among geographically different isolates were insignificant, we mean that the evolutionary distance by ITS sequences within Hungarian Cryphonectria parasitica isolates is too small to get well based consequences for the phylogenetic relationships.